Pengaruh Metode Springate dalam Memprediksi Financial Distress pada Perusahaan Konstruksi yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2021-2024 - Silmi Azhaar Istiqomah; Rendi Kusuma Natita (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to analyxe the effect of Working Capital to Total Assets, Earning Before Interest and Taxes to Total Assets, Earning Before Taxes to Current Liabilities, and Sales to Total Assets on Financial Distress, as measured using the Springate model, in construction companies listed on the Indonesia Stock Exchange for the 2021-2024 period. This study uses a quantitative approach with multiple linear regression methods on 32 obrervations selected through puroosive sampling. The data used are secondary data in the form of audited annual financial reports, The results show that all independent variables have a significance level below 0,05. The variable Earning Before Taxes to Current Liabilities is proven to be the most dominant variable in influencing financial distress. The coefficient of determination value indicates that the model is able to adequately explain variations in financial distress. This finding indicates that financial ratios play an important role in detecting and predicting financial distress in conctruction companies.